Effects of ringing, interstocks and twisted root systems treatments in pear, cv. Seleta - Sampaio, V.R. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1990)
Vegetative growth and first production of pear cv. Seleta were observed when submitted to various treatments: a) plants from cuttings were submitted to various ringing treatments after planting b) plants from cuttings having the root system twisted and c) plants double grafted in 'Le Conte' rootstock, with 'Garber' and 'Kieffer' as interstocks. After 5.5 years from planting of the 10 treatments in the field the conclusions were: 1) ringing and interstocks treatments did not interfere in the pear vegetative growth, 2) twisted root systems plants had normal growth development after planting in the field and 3) pear plants had their first production with the same age, independently of the treatments.